Mama Miti : Wangari Maathai and the Trees of Kenya - Donna Jo Napoli (New York Simon & Schuster, 2010)
Through artful prose and beautiful illustrations, Donna Jo Napoli and Kadir Nelson tell the true story of Wangari Muta Maathai, known as "Mama Miti," who in 1977 founded the Green Belt Movement, an African grassroots organization that has empowered many people to mobilize and combat deforestation, soil erosion, and environmental degradation. Today more than 30 million trees have been planted throughout Mama Miti's native Kenya, and in 2004 she became the first African woman to win the Nobel Peace Prize. Wangari Muta Maathai has changed Kenya tree by tree--and with each page turned, children will realize their own ability to positively impact the future.
Keywords: Environment - peace - Nature - Culture - peace; Circle Time -- Environment - peace - Nature - Culture - peace